2010
DOI: 10.1103/physrevb.81.054306
|View full text |Cite
|
Sign up to set email alerts
|

Landau-Zener problem with waiting at the minimum gap and related quench dynamics of a many-body system

Abstract: We discuss a technique for solving the Landau-Zener (LZ) problem of finding the probability of excitation in a two-level system. The idea of time reversal for the Schrödinger equation is employed to obtain the state reached at the final time and hence the excitation probability. Using this method, which can reproduce the well-known expression for the LZ transition probability, we solve a variant of the LZ problem which involves waiting at the minimum gap for a time tw; we find an exact expression for the excit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Refs. (Damski and Zurek, 2006;Divakaran et al, 2010) for particular cases). Likewise if there is a discontinuity in the second order derivative of g(t) asymptotically the transition probability in the LZ problem scales quadratically with acceleration.…”
Section: Slow Dynamics In Gapped and Gapless Systemsmentioning
confidence: 99%
“…Refs. (Damski and Zurek, 2006;Divakaran et al, 2010) for particular cases). Likewise if there is a discontinuity in the second order derivative of g(t) asymptotically the transition probability in the LZ problem scales quadratically with acceleration.…”
Section: Slow Dynamics In Gapped and Gapless Systemsmentioning
confidence: 99%
“…We now consider a similar problem where the parameter J − is varied linearly up to the critical point at which the variation is stopped for some time t w [555]. After this waiting time t w , the variation is once again resumed in the forward direction.…”
Section: (F) Generalized Quenching Schemesmentioning
confidence: 99%
“…A study of the Landau-Zener problem with waiting at the minimum gap has been reported in Ref. [25]. It was observed that the waiting influences the excitation probability.…”
Section: Free Evolution and Decay Of Fidelitymentioning
confidence: 99%